Rheumatoid arthritis associated pulmonary hypertension: Clinical challenges reflecting the diversity of pathophysiology. (2017) - Panagiotidou, Evangelia; Sourla, Evdokia; Kotoulas, Serafim Xrisovalantis; Akritidou, Sofia; Bikos, Vasileios; Bagalas, Vasileios; Stanopoulos, Ioannis; Pitsiou, Georgia
Abstract: The present article reports three clinical cases in order to elucidate the diversity of the pathophysiological mechanisms that underlie rheumatoid arthritis associated pulmonary hypertension. The condition's three major causes are: interstitial lung disease, vasculitis, and chronic thromboembolic disease, but it should be noted that the multiple pulmonary manifestations of rheumatoid arthritis, can all contribute to chronic lung disease or hypoxia. The first patient in this report suffered from moderate restriction due to fibrosis and was diagnosed with pulmonary hypertension during an episode of life threatening hypoxia. Early upfront combination therapy prevented intubation and reversed hypoxia to adequate levels. The second presented patient was a case of isolated pulmonary hypertension attributable to vasculopathy. The patient maintained normal lung volumes but low diffusion capacity and echocardiography dictated the need for right heart catheterization. Finally, the third patient presented severe functional limitation due to several manifestations of rheumatoid arthritis, but a past episode of acute pulmonary embolism was also reported although it had never been evaluated. Chronic thromboembolic disease was eventually proved to be one major cause of the patient's pulmonary hypertension. The importance of early identification of pulmonary hypertension in patients with rheumatoid arthritis is therefore emphasized, especially since multiple treatment options are available, symptoms can be treated, and right heart failure can be avoided.